Płaczcie – umarł Pan… Nazwy własne we wczesno-barokowym poemacie pasyjnym (na przykładzie Pamiątki krwawej ofiary Pana Zbawiciela naszego Jezusa Chrystusa Abrahama Rożniatowskiego) - Rejter, Artur (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2017)
The article is dedicated to description of proper names functions in chosen narrative poem of Passion literature of Polish Baroque. Analyzed proper names in Pamiątka krwawej ofiary Pana Zbawiciela naszego Jezusa Chrystusa (1610) by Abraham Rożniatowski are mainly connected with metaphysical sphere of culture, majority of them is conventional, primarily drawn from Bible. The main function of proper names is to describe the Passion in influential way and to show the people how grievous and savage it was. The onomastic field of the narrative poem is strictly related to religious cult of Kalwaria Zebrzydowska popular in Poland in Baroque times.